Virulence Genes Profile of Escherichia coli Isolated from Urinary Catheterized and Non-Catheterized Patients - Abdul-Ghaffar , Saba Nazeih; Abu-Risha, Rasmia Abed (Iraqi Journal of Science, 2022)
The severity of UTI produced by E. coli is due to the expression of a widespectrum of virulence factors. In this study the role of E. coli virulence determinantsin the pathogenesis of UTI in urinary catheterized and non-catheterized patients hasbeen evaluated. The isolates were recovered from 129 patients admitted to thehospital. Virulence genes of E. coli were detected by polymerase chain reactionanalysis for the prevalence of these virulence factors. The targeted geneticdeterminants were those coding for Type 1 fimbriae, Pyelonephritis-Associated Pili(PAP), Antigen 43 (Ag43), α-Hemolysin and Aerobactin siderophores among thestudied isolates. The prevalence of genes fimH, papC, ang43, hlyA and iutA were88.37%, 72.09%, 18.60%, 51.16% and 79.06% respectively. The fimH gene with88.37% had a highest prevalence of virulence genes in patients with UTIs.Statistically in the present study, there was no significant difference in theprevalence of genes profiles of E. coli isolates causing UTI in non-catheterized andcatheterized patients. However, all the studied strains exhibited 16 virulence genepatterns; among the strains isolated from patients with urinary catheter showedmultitude and greatest diversity of genes patterns than strains from non-catheterizedpatients.